Has Europe been catching up? An industry level analysis of venture capital success over 1985 - 2009 - Roman Kräussl; Stefan Krause (Goethe University Frankfurt, Center for Financial Studies (CFS), 2012)
After nearly two decades of US leadership during the 1980s and 1990s, are Europe's venture capital (VC) markets in the 2000s finally catching up regarding the provision of financing and successful exits, or is the performance gap as wide as ever? Are we amid an overall VC performance slump with no encouraging news? We attempt to answer these questions by tracking over 40,000 VC-backed firms stemming from six industries in 13 European countries and the US between 1985 and 2009; determining the type of exit - if any - each particular firm's investors choose for the venture.
urn:nbn:de:hebis:30:3-286311
Keywords: G24; G3; 330; Venture Capital; Private Equity; Entrepreneurial Activity; Performance Gap